An overview of the mechanisms and bases of insect resistance in maize - Smith, C.M.
Sumario (En)
Ilus.; 111 ref.
Keywords: ZEA MAYS; GENOTIPOS; FITOMEJORAMIENTO; RESISTENCIA A LAS PLAGAS; INSECTA; CONTROL DE PLAGAS; METODOS DE CONTROL DE PLAGAS